142k views
19 votes
F(x) = -2x + 2

g(x) = 3x^2– 3x
Find f (4) and g(-3)
helpp please i would appreciate it

F(x) = -2x + 2 g(x) = 3x^2– 3x Find f (4) and g(-3) helpp please i would appreciate-example-1
User Kaelen
by
5.7k points

1 Answer

0 votes

Answer:

f(4) = -6, g(-3) = 36

Explanation:

To find f(#) or g(#), plug the number into each x of the equation.

f(x) = -2x + 2

f(4) = -2(4) + 2

Simplify the parentheses by multiplying.

f(4) = -8 + 2

Add.

f(4) = -6

g(x) = 3x² - 3x

g(-3) = 3(-3)² - 3(-3)

Simplify the exponent first.

g(-3) = 3(9) - 3(-3)

Simplify the parentheses by multiplying.

g(-3) = 27 + 9

Add.

g(-3) = 36

User PeerBr
by
5.2k points